Anti-seismic corrosion-resistant light composite building material and preparation method thereof

By using composite building materials with high-performance raw materials such as cement, light aggregate, corrosion-resistant fibers and modified epoxy resin, the shortcomings of traditional building materials in terms of earthquake resistance, corrosion resistance and lightweight are solved, and efficient earthquake resistance, corrosion resistance and lightweight effects are achieved.

CN119638337AInactive Publication Date: 2025-03-18HAIKOU XINYIXING IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964560.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional building materials have shortcomings in terms of earthquake resistance, corrosion resistance and lightweight, which is difficult to meet the demand for high-performance building materials in modern buildings.

Method used

A shock-resistant and corrosion-resistant lightweight composite building material is used, which consists of a variety of high-performance raw materials such as cement, light aggregate, corrosion-resistant fibers, modified epoxy resin, etc., and is added with anti-seismic enhancer and composite inorganic-organic preservatives to improve its comprehensive performance.

Benefits of technology

It achieves significant seismic resistance and corrosion resistance, and has lightweight properties, which reduces the load and seismic force of the building, ensures the long-term stability of the building materials, and reflects the design concept of environmental protection and sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638337A_ABST
    Figure CN119638337A_ABST
Patent Text Reader

Abstract

The invention provides an anti-seismic corrosion-resistant lightweight composite building material and a preparation method thereof, the building material is composed of cement, lightweight aggregate, corrosion-resistant fiber, modified epoxy resin and other raw materials according to a specific proportion, and the anti-seismic, corrosion-resistant and lightweight characteristics of the building material are realized. Wherein the flexible chain segment modifier, the flexibilizer, the flame retardant, the catalyst and other components are added into the modified epoxy resin, so that the flexibility and anti-seismic property of the resin are improved. The preparation method of the building material comprises the steps of raw material preparation, mixing and stirring, forming and curing, post-treatment and the like, and the quality and performance of the building material are ensured. The anti-seismic corrosion-resistant light composite building material is particularly suitable for the fields of high-rise buildings, underground engineering, ocean and chemical engineering facilities, bridge and road engineering, special buildings and the like, can provide excellent structural safety and durability, reduces the maintenance cost, and has wide application prospects and market value. The building material is simple in preparation method, low in cost and easy to popularize and apply.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of novel composite building materials, and specifically discloses an earthquake-resistant and corrosion-resistant lightweight composite building material and a preparation method thereof. Background Art

[0002] In today's rapidly developing construction industry, the performance requirements for building materials are becoming increasingly stringent, especially in terms of earthquake resistance, corrosion resistance and lightweight. Although traditional building materials, such as ordinary concrete and masonry structures, can meet construction needs to a certain extent, they often have many shortcomings.

[0003] First, traditional concrete materials have high density and heavy weight, which not only increases the load on buildings, but also shows poor seismic performance in natural disasters such as earthquakes. Its brittle characteristics make it easy to crack and collapse under vibration, seriously threatening people's lives and property.

[0004] Secondly, many building materials are prone to deterioration in humid, salt spray or chemical corrosion environments, such as steel rust and concrete spalling, which not only shortens the service life of the building but also increases maintenance costs. This problem is particularly prominent in highly corrosive environments such as marine engineering and chemical facilities.

[0005] In addition, with the pursuit of lightweight and energy-saving in modern buildings, traditional heavy building materials can no longer meet new design concepts. Lightweight building materials can not only reduce the weight of buildings and reduce earthquake forces, but also improve construction efficiency and reduce transportation costs.

[0006] In response to the above problems, although some new building materials have appeared in the market, such as lightweight concrete and aerated concrete, these materials still have certain limitations in terms of earthquake resistance, corrosion resistance or lightweight. For example, although some lightweight building materials have reduced their own weight, their earthquake resistance is poor; or although they have certain corrosion resistance, their density is still high, which is not conducive to the lightweight design of buildings.

[0007] Therefore, there is an urgent need for a new type of composite building material that can meet the requirements of earthquake resistance and corrosion resistance and has lightweight characteristics, so as to overcome the shortcomings of existing technologies, improve the safety and durability of buildings, and reduce the cost of the entire life cycle. Summary of the invention

[0008] In view of the deficiencies in the prior art, the present invention provides an earthquake-resistant and corrosion-resistant lightweight composite building material and a preparation method thereof.

[0009] The present invention includes the following technical solutions:

[0010] A seismic and corrosion-resistant lightweight composite building material, the composite building material is composed of the following raw materials in parts by weight:

[0011]

[0012] Furthermore, in the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material, the cement is ordinary Portland cement, and its strength grade is not less than 42.5.

[0013] Furthermore, in the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material, the lightweight aggregate is expanded perlite, and its bulk density is not more than 200 kg / m 3 , and the particle size distribution is between 0.5mm and 5mm.

[0014] Furthermore, in the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material, the corrosion-resistant fiber is glass fiber, in the form of untwisted or slightly twisted continuous filaments, with a single filament diameter ranging from 6 microns to 24 microns, a fiber strength of not less than 3000 MPa, and an elongation at break controlled between 1.5% and 3.5%.

[0015] Furthermore, in the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material, the polymer resin is a modified epoxy resin, which is modified from the following components in parts by weight, and comprises the following steps:

[0016] 1) Select epoxy resin base material: 100 parts of bisphenol A epoxy resin is used as the base material, and its epoxy equivalent is 180-200g / eq;

[0017] 2) Adding a flexible segment modifier: Add 10-30 parts of polyethylene glycol PEG-4000 to the epoxy resin base material, and mix them evenly by mechanical stirring or heating and melting to improve the flexibility and impact resistance of the resin;

[0018] 3) Adding toughening agent: Add 5-15 parts of core-shell rubber particles as toughening agent, and evenly disperse them in the resin by high-speed mixer or ultrasonic treatment to further enhance the toughness and shock resistance of the resin;

[0019] 4) Mixing flame retardant: Add 1-5 parts of brominated epoxy resin flame retardant;

[0020] 5) Adding catalyst: Finally, add 0.5-2 parts of catalyst dimethylbenzylamine to promote the curing reaction of epoxy resin;

[0021] 6) Mixing and curing: After all the above components are mixed evenly, the resin system is cross-linked and cured by heating at 80-120°C to form a modified epoxy resin.

[0022] Furthermore, in the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material, the earthquake-resistant reinforcing agent is waste tire rubber particles with a particle size between 0.5 mm and 2 mm.

[0023] Furthermore, in the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material, the preservative is a composite inorganic-organic preservative, comprising zinc salts, silicates and organic amine compounds; preferably, it includes: zinc borate, accounting for 35% of the total amount of the preservative, used to inhibit the growth of microorganisms and provide long-term antibacterial protection; sodium metasilicate, accounting for 25% of the total amount of the preservative, enhancing the structural strength of the building material and improving corrosion resistance; dodecyl dimethyl benzyl ammonium chloride, accounting for 15% of the total amount of the preservative, synergistically acting with the inorganic components to form a comprehensive anti-corrosion barrier.

[0024] Furthermore, in the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material, the water reducing agent is a high-efficiency polycarboxylic acid-based water reducing agent, and the water reduction rate is not less than 25%.

[0025] The present invention also discloses a method for preparing an earthquake-resistant and corrosion-resistant lightweight composite building material, comprising the following steps:

[0026] S1 Raw material preparation: weigh cement, lightweight aggregate, corrosion-resistant fiber, high molecular polymer resin, seismic enhancer, preservative, water reducer and water according to the formula;

[0027] S2 Mixing and stirring:

[0028] First, cement, lightweight aggregate, seismic reinforcement and corrosion-resistant fiber are added into a mixer for preliminary mixing, and the stirring speed is controlled at 100-200rpm to avoid fiber breakage;

[0029] Then, slowly add water while continuing to stir to ensure that all solid ingredients are fully wetted;

[0030] Next, add the prepared high molecular polymer resin and continue stirring until the resin is evenly dispersed in the mixture;

[0031] Finally, add the preservatives and water reducer and stir thoroughly again to ensure that all ingredients are evenly mixed;

[0032] S3 molding and curing:

[0033] Pour the mixed material into the mold and shape it according to the required shape and size;

[0034] Properly vibrate the mold to eliminate bubbles in the material and improve the density of the building material;

[0035] Place the mold in a constant temperature and humidity environment for natural curing or heating curing, with the temperature controlled between 80-120°C until the building material is completely cured;

[0036] S4 post-processing:

[0037] After curing is complete, the building material is removed from the mold and necessary trimming and cutting is performed.

[0038] The invention also discloses the use of the earthquake-resistant and corrosion-resistant lightweight composite building material in high-rise buildings, underground projects, marine and chemical facilities, bridges and road projects, and special buildings.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The present invention proposes an earthquake-resistant and corrosion-resistant lightweight composite building material and a preparation method thereof, wherein the building material combines a variety of high-performance raw materials such as cement, lightweight aggregate, corrosion-resistant fiber, modified epoxy resin, and adds an earthquake-resistant reinforcing agent and a composite inorganic-organic preservative to improve its comprehensive performance. The prepared composite building material not only has significant earthquake resistance and excellent corrosion resistance, but also achieves lightweight characteristics, reducing the load and seismic force of the building. At the same time, its high strength and durability ensure the long-term stability of the building material, and the environmentally friendly and sustainable design concept also reflects a friendly attitude towards the environment. This composite building material is widely used in many fields such as high-rise buildings, underground projects, marine and chemical facilities, etc., providing excellent solutions for the diversified needs of the construction industry, significantly improving the safety and durability of buildings, reducing the full life cycle cost, and has broad market application prospects and significant social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Comparison of the compressive strength (Mpa) of the building materials of Examples 1-3 and Comparative Examples 1-3;

[0042] Figure 2 Comparison of the flexural strength (Mpa) of the building materials of Examples 1-3 and Comparative Examples 1-3;

[0043] Figure 3 Comparison of the tensile strength (Mpa) of the building materials of Examples 1-3 and Comparative Examples 1-3;

[0044] Figure 4 The density (g / cm 2 ) comparison. DETAILED DESCRIPTION

[0045] .A seismic and corrosion-resistant lightweight composite building material, the composite building material is composed of the following raw materials in parts by weight:

[0046] 50-80 parts of cement

[0047] Lightweight aggregate: 20-40 parts perlite or expanded vermiculite

[0048] Corrosion-resistant fiber: 5-15 parts of glass fiber or carbon fiber

[0049] 5-15 parts of polymer resin

[0050] Anti-seismic enhancer: 3-10 parts of rubber particles or elastomer particles

[0051] 1-5 parts of preservative

[0052] Water reducing agent 0.5-3 parts

[0053] 20-40 parts of water.

[0054] The cement is ordinary Portland cement, and its strength grade is not less than 42.5;

[0055] The lightweight aggregate is expanded perlite, and its bulk density is not more than 200kg / m 3 , and the particle size distribution is between 0.5mm and 5mm.

[0056] The corrosion-resistant fiber is glass fiber in the form of untwisted or slightly twisted continuous filaments, with a single filament diameter ranging from 6 microns to 24 microns, a fiber strength of not less than 3000 MPa, and an elongation at break controlled between 1.5% and 3.5%.

[0057] The high molecular polymer resin is a modified epoxy resin, which is modified from the following components in parts by weight, and comprises the following steps:

[0058] 1) Select epoxy resin base material: 100 parts of bisphenol A epoxy resin is used as the base material, and its epoxy equivalent is 180-200g / eq;

[0059] 2) Adding a flexible segment modifier: Add 10-30 parts of polyethylene glycol PEG-4000 to the epoxy resin base material, and mix them evenly by mechanical stirring or heating and melting to improve the flexibility and impact resistance of the resin;

[0060] 3) Adding toughening agent: Add 5-15 parts of core-shell rubber particles as toughening agent, and evenly disperse them in the resin by high-speed mixer or ultrasonic treatment to further enhance the toughness and shock resistance of the resin;

[0061] 4) Mixing flame retardant: Add 1-5 parts of brominated epoxy resin flame retardant;

[0062] 5) Adding catalyst: Finally, add 0.5-2 parts of catalyst dimethylbenzylamine to promote the curing reaction of epoxy resin;

[0063] 6) Mixing and curing: After all the above components are mixed evenly, the resin system is cross-linked and cured by heating at 80-120°C to form a modified epoxy resin.

[0064] The anti-seismic enhancer is waste tire rubber particles with a particle size between 0.5 mm and 2 mm.

[0065] The preservatives include: zinc borate, accounting for 35% of the total amount of preservatives, used to inhibit the growth of microorganisms and provide long-term antibacterial protection; sodium metasilicate, accounting for 25% of the total amount of preservatives, enhancing the structural strength of building materials and improving corrosion resistance; dodecyl dimethyl benzyl ammonium chloride, accounting for 15% of the total amount of preservatives, synergistically working with inorganic components to form a comprehensive anti-corrosion barrier.

[0066] The water reducing agent is a high-efficiency polycarboxylic acid-based water reducing agent, and the water reducing rate is not less than 25%.

[0067] The method for preparing the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material comprises the following steps:

[0068] S1 Raw material preparation: weigh cement, lightweight aggregate, corrosion-resistant fiber, high molecular polymer resin, seismic enhancer, preservative, water reducer and water according to the formula;

[0069] S2 Mixing and stirring:

[0070] First, cement, lightweight aggregate, seismic reinforcement and corrosion-resistant fiber are added into a mixer for preliminary mixing, and the stirring speed is controlled at 100-200rpm to avoid fiber breakage;

[0071] Then, slowly add water while continuing to stir to ensure that all solid ingredients are fully wetted;

[0072] Next, add the prepared high molecular polymer resin and continue stirring until the resin is evenly dispersed in the mixture;

[0073] Finally, add the preservatives and water reducer and stir thoroughly again to ensure that all ingredients are evenly mixed;

[0074] S3 molding and curing:

[0075] Pour the mixed material into the mold and shape it according to the required shape and size;

[0076] Properly vibrate the mold to eliminate bubbles in the material and improve the density of the building material;

[0077] Place the mold in a constant temperature and humidity environment for natural curing or heating curing, with the temperature controlled between 80-120°C until the building material is completely cured;

[0078] S4 post-processing:

[0079] After curing is complete, the building material is removed from the mold and necessary trimming and cutting is performed.

[0080] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0081] Embodiment 1:

[0082] .A seismic and corrosion-resistant lightweight composite building material, the composite building material is composed of the following raw materials in parts by weight:

[0083] 50 parts cement

[0084] Lightweight aggregate: 20 parts perlite or expanded vermiculite

[0085] Corrosion-resistant fiber: 5 parts of glass fiber or carbon fiber

[0086] 5 parts of polymer resin

[0087] Anti-seismic enhancer: 3 parts of rubber particles or elastomer particles

[0088] 1 part preservative

[0089] 0.5 parts of water reducing agent

[0090] 20 parts water.

[0091] The cement is ordinary Portland cement, and its strength grade is not less than 42.5;

[0092] The lightweight aggregate is expanded perlite, and its bulk density is not more than 200kg / m 3 , and the particle size distribution is between 0.5mm and 5mm.

[0093] The corrosion-resistant fiber is glass fiber in the form of untwisted or slightly twisted continuous filaments, with a single filament diameter ranging from 6 microns to 24 microns, a fiber strength of not less than 3000 MPa, and an elongation at break controlled between 1.5% and 3.5%.

[0094] The high molecular polymer resin is a modified epoxy resin, which is modified from the following components in parts by weight, and comprises the following steps:

[0095] 1) Select epoxy resin base material: 100 parts of bisphenol A epoxy resin is used as the base material, and its epoxy equivalent is 180-200g / eq;

[0096] 2) Adding a flexible segment modifier: Add 20 parts of polyethylene glycol PEG-4000 to the epoxy resin base material and mix them evenly by mechanical stirring or heating and melting to improve the flexibility and impact resistance of the resin;

[0097] 3) Adding toughening agent: Add 10 parts of core-shell rubber particles as toughening agent, and evenly disperse them in the resin by high-speed mixer or ultrasonic treatment to further enhance the toughness and shock resistance of the resin;

[0098] 4) Mixing flame retardant: Add 2.5 parts of brominated epoxy resin flame retardant;

[0099] 5) Adding catalyst: Finally, add 1 part of catalyst dimethylbenzylamine to promote the curing reaction of epoxy resin;

[0100] 6) Mixing and curing: After all the above components are mixed evenly, the resin system is cross-linked and cured by heating at 100° C. to form a modified epoxy resin.

[0101] The anti-seismic enhancer is waste tire rubber particles with a particle size between 0.5 mm and 2 mm.

[0102] The preservatives include: zinc borate, accounting for 35% of the total amount of preservatives, used to inhibit the growth of microorganisms and provide long-term antibacterial protection; sodium metasilicate, accounting for 25% of the total amount of preservatives, enhancing the structural strength of building materials and improving corrosion resistance; dodecyl dimethyl benzyl ammonium chloride, accounting for 15% of the total amount of preservatives, synergistically working with inorganic components to form a comprehensive anti-corrosion barrier.

[0103] The water reducing agent is a high-efficiency polycarboxylic acid-based water reducing agent, and the water reducing rate is not less than 25%.

[0104] The method for preparing the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material comprises the following steps:

[0105] S1 Raw material preparation: weigh cement, lightweight aggregate, corrosion-resistant fiber, high molecular polymer resin, seismic enhancer, preservative, water reducer and water according to the formula;

[0106] S2 Mixing and stirring:

[0107] First, cement, lightweight aggregate, seismic reinforcement and corrosion-resistant fiber are added into a mixer for preliminary mixing, and the stirring speed is controlled at 100-200rpm to avoid fiber breakage;

[0108] Then, slowly add water while continuing to stir to ensure that all solid ingredients are fully wetted;

[0109] Next, add the prepared high molecular polymer resin and continue stirring until the resin is evenly dispersed in the mixture;

[0110] Finally, add the preservatives and water reducer and stir thoroughly again to ensure that all ingredients are evenly mixed;

[0111] S3 molding and curing:

[0112] Pour the mixed material into the mold and shape it according to the required shape and size;

[0113] Properly vibrate the mold to eliminate bubbles in the material and improve the density of the building material;

[0114] Place the mold in a constant temperature and humidity environment for natural curing or heating curing, with the temperature controlled between 80-120°C until the building material is completely cured;

[0115] S4 post-processing:

[0116] After curing is complete, the building material is removed from the mold and necessary trimming and cutting is performed.

[0117] Example 2

[0118] .A seismic and corrosion-resistant lightweight composite building material, the composite building material is composed of the following raw materials in parts by weight:

[0119]

[0120] The cement is ordinary Portland cement, and its strength grade is not less than 42.5;

[0121] The lightweight aggregate is expanded perlite, and its bulk density is not more than 200kg / m 3 , and the particle size distribution is between 0.5mm and 5mm.

[0122] The corrosion-resistant fiber is glass fiber in the form of untwisted or slightly twisted continuous filaments, with a single filament diameter ranging from 6 microns to 24 microns, a fiber strength of not less than 3000 MPa, and an elongation at break controlled between 1.5% and 3.5%.

[0123] The high molecular polymer resin is a modified epoxy resin, which is modified from the following components in parts by weight, and comprises the following steps:

[0124] 1) Select epoxy resin base material: 100 parts of bisphenol A epoxy resin is used as the base material, and its epoxy equivalent is 180-200g / eq;

[0125] 2) Adding a flexible segment modifier: Add 20 parts of polyethylene glycol PEG-4000 to the epoxy resin base material and mix them evenly by mechanical stirring or heating and melting to improve the flexibility and impact resistance of the resin;

[0126] 3) Adding toughening agent: Add 10 parts of core-shell rubber particles as toughening agent, and evenly disperse them in the resin by high-speed mixer or ultrasonic treatment to further enhance the toughness and shock resistance of the resin;

[0127] 4) Mixing flame retardant: Add 2.5 parts of brominated epoxy resin flame retardant;

[0128] 5) Adding catalyst: Finally, add 1 part of catalyst dimethylbenzylamine to promote the curing reaction of epoxy resin;

[0129] 6) Mixing and curing: After all the above components are mixed evenly, the resin system is cross-linked and cured by heating at 100° C. to form a modified epoxy resin.

[0130] The anti-seismic enhancer is waste tire rubber particles with a particle size between 0.5 mm and 2 mm.

[0131] The preservatives include: zinc borate, accounting for 35% of the total amount of preservatives, used to inhibit the growth of microorganisms and provide long-term antibacterial protection; sodium metasilicate, accounting for 25% of the total amount of preservatives, enhancing the structural strength of building materials and improving corrosion resistance; dodecyl dimethyl benzyl ammonium chloride, accounting for 15% of the total amount of preservatives, synergistically working with inorganic components to form a comprehensive anti-corrosion barrier.

[0132] The water reducing agent is a high-efficiency polycarboxylic acid-based water reducing agent, and the water reducing rate is not less than 25%.

[0133] The method for preparing the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material comprises the following steps:

[0134] S1 Raw material preparation: weigh cement, lightweight aggregate, corrosion-resistant fiber, high molecular polymer resin, seismic enhancer, preservative, water reducer and water according to the formula;

[0135] S2 Mixing and stirring:

[0136] First, cement, lightweight aggregate, seismic reinforcement and corrosion-resistant fiber are added into a mixer for preliminary mixing, and the stirring speed is controlled at 100-200rpm to avoid fiber breakage;

[0137] Then, slowly add water while continuing to stir to ensure that all solid ingredients are fully wetted;

[0138] Next, add the prepared high molecular polymer resin and continue stirring until the resin is evenly dispersed in the mixture;

[0139] Finally, add the preservatives and water reducer and stir thoroughly again to ensure that all ingredients are evenly mixed;

[0140] S3 molding and curing:

[0141] Pour the mixed material into the mold and shape it according to the required shape and size;

[0142] Properly vibrate the mold to eliminate bubbles in the material and improve the density of the building material;

[0143] Place the mold in a constant temperature and humidity environment for natural curing or heating curing, with the temperature controlled between 80-120°C until the building material is completely cured;

[0144] S4 post-processing:

[0145] After curing is complete, the building material is removed from the mold and necessary trimming and cutting is performed.

[0146] Example 3

[0147] .A seismic and corrosion-resistant lightweight composite building material, the composite building material is composed of the following raw materials in parts by weight:

[0148] 80 parts of cement

[0149] Lightweight aggregate: 40 parts perlite or expanded vermiculite

[0150] Corrosion-resistant fiber: 15 parts of glass fiber or carbon fiber

[0151] 15 parts of polymer resin

[0152] Anti-seismic enhancer: 10 parts of rubber particles or elastomer particles

[0153] 5 parts of preservative

[0154] 3 parts of water reducing agent

[0155] 40 parts of water.

[0156] The cement is ordinary Portland cement, and its strength grade is not less than 42.5;

[0157] The lightweight aggregate is expanded perlite, and its bulk density is not more than 200kg / m 3 , and the particle size distribution is between 0.5mm and 5mm.

[0158] The corrosion-resistant fiber is glass fiber in the form of untwisted or slightly twisted continuous filaments, with a single filament diameter ranging from 6 microns to 24 microns, a fiber strength of not less than 3000 MPa, and an elongation at break controlled between 1.5% and 3.5%.

[0159] The high molecular polymer resin is a modified epoxy resin, which is modified from the following components in parts by weight, and comprises the following steps:

[0160] 1) Select epoxy resin base material: 100 parts of bisphenol A epoxy resin is used as the base material, and its epoxy equivalent is 180-200g / eq;

[0161] 2) Adding a flexible segment modifier: Add 20 parts of polyethylene glycol PEG-4000 to the epoxy resin base material and mix them evenly by mechanical stirring or heating and melting to improve the flexibility and impact resistance of the resin;

[0162] 3) Adding toughening agent: Add 10 parts of core-shell rubber particles as toughening agent, and evenly disperse them in the resin by high-speed mixer or ultrasonic treatment to further enhance the toughness and shock resistance of the resin;

[0163] 4) Mixing flame retardant: Add 2.5 parts of brominated epoxy resin flame retardant;

[0164] 5) Adding catalyst: Finally, add 1 part of catalyst dimethylbenzylamine to promote the curing reaction of epoxy resin;

[0165] 6) Mixing and curing: After all the above components are mixed evenly, the resin system is cross-linked and cured by heating at 100° C. to form a modified epoxy resin.

[0166] The anti-seismic enhancer is waste tire rubber particles with a particle size between 0.5 mm and 2 mm.

[0167] The preservatives include: zinc borate, accounting for 35% of the total amount of preservatives, used to inhibit the growth of microorganisms and provide long-term antibacterial protection; sodium metasilicate, accounting for 25% of the total amount of preservatives, enhancing the structural strength of building materials and improving corrosion resistance; dodecyl dimethyl benzyl ammonium chloride, accounting for 15% of the total amount of preservatives, synergistically working with inorganic components to form a comprehensive anti-corrosion barrier.

[0168] The water reducing agent is a high-efficiency polycarboxylic acid-based water reducing agent, and the water reducing rate is not less than 25%.

[0169] The method for preparing the above-mentioned earthquake-resistant and corrosion-resistant lightweight composite building material comprises the following steps:

[0170] S1 Raw material preparation: weigh cement, lightweight aggregate, corrosion-resistant fiber, high molecular polymer resin, seismic enhancer, preservative, water reducer and water according to the formula;

[0171] S2 Mixing and stirring:

[0172] First, cement, lightweight aggregate, seismic reinforcement and corrosion-resistant fiber are added into a mixer for preliminary mixing, and the stirring speed is controlled at 100-200rpm to avoid fiber breakage;

[0173] Then, slowly add water while continuing to stir to ensure that all solid ingredients are fully wetted;

[0174] Next, add the prepared high molecular polymer resin and continue stirring until the resin is evenly dispersed in the mixture;

[0175] Finally, add the preservatives and water reducer and stir thoroughly again to ensure that all ingredients are evenly mixed;

[0176] S3 molding and curing:

[0177] Pour the mixed material into the mold and shape it according to the required shape and size;

[0178] Properly vibrate the mold to eliminate bubbles in the material and improve the density of the building material;

[0179] Place the mold in a constant temperature and humidity environment for natural curing or heating curing, with the temperature controlled between 80-120°C until the building material is completely cured;

[0180] S4 post-processing:

[0181] After curing is complete, the building material is removed from the mold and necessary trimming and cutting is performed.

[0182] Comparative Example 1

[0183] The high molecular polymer resin uses bisphenol A epoxy resin without modification, and the rest is the same as in Example 2.

[0184] Comparative Example 2

[0185] The corrosion-resistant fiber is not contained, and the rest is the same as in Example 2.

[0186] Comparative Example 3

[0187] Ordinary lightweight bricks available on the market.

[0188] Test Case

[0189] The composite building materials of Examples 1-3 and Comparative Examples 1-3 were prepared into the same test blocks and subjected to the following performance tests.

[0190] Compressive strength: Test the maximum bearing capacity of building materials under compression to evaluate their structural strength. (Refer to GB / T 50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete")

[0191] Flexural strength: measures the resistance of building materials under bending force, reflecting their flexibility and durability. (Refer to GB / T 17671-1999 "Test method for strength of cement mortar (ISO method)")

[0192] Tensile strength: Evaluate the performance of building materials under tensile stress, especially the fiber reinforcement effect. (Refer to the test method of splitting tensile strength in GB / T50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete")

[0193] Salt spray test: Place the building materials in a salt spray environment to simulate the marine or corrosive atmosphere to evaluate their corrosion resistance. (Refer to GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test") 60℃, 96h, 5% hydrochloric acid accelerated test.

[0194] Density measurement: Directly measure the density of building materials to assess their lightweightness.

[0195] The test results are shown in Table 1 and Figure 1-4 .

[0196] Table 1 Comprehensive test results of composite building materials

[0197]

[0198]

[0199] Through comprehensive analysis of the data in Table 1, we can clearly see that the earthquake-resistant and corrosion-resistant lightweight composite building materials (Examples 1-3) using the technical solution of the present invention are significantly better than the comparative examples in terms of compressive strength (up to 40.98MPa), flexural strength (up to 26.38MPa), tensile strength (up to 357MPa) and corrosion resistance (no corrosion after salt spray test). At the same time, these building materials maintain a low density (ranging from 2.16g / cm 3 Up to 2.23g / cm 3 ), achieving the goal of lightweight. These excellent performances are mainly attributed to two key innovations in the present invention: first, the polymer resin is modified by adding components such as flexible segment modifiers, toughening agents, flame retardants and catalysts, which significantly improves the flexibility and seismic resistance of the resin; second, corrosion-resistant fibers are added (up to 15%). These fibers not only enhance the tensile strength of the building materials (up to nearly 150% compared to the control group), but also significantly improve their corrosion resistance. The combined effect of these two technological innovations enables the building materials of the present invention to maintain lightweight (the lowest density is only 2.16g / cm 3 ), while achieving a significant improvement in multiple properties such as earthquake resistance and corrosion resistance, overcoming the limitations of traditional building materials in terms of earthquake resistance, corrosion resistance or lightweight. Therefore, the technical solution of the present invention shows a high degree of creativity and practical value in the field of new composite building materials, and provides an effective solution to the urgent demand for high-performance building materials in the construction industry.

[0200] The above are limited to several preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A seismic and corrosion-resistant lightweight composite building material, characterized in that: The composite building material is composed of the following raw materials by weight: 50-80 parts of cement Lightweight aggregate: 20-40 parts perlite or expanded vermiculite Corrosion-resistant fiber: 5-15 parts of glass fiber or carbon fiber 5-15 parts of polymer resin Anti-seismic enhancer: 3-10 parts of rubber particles or elastomer particles 1-5 parts of preservative Water reducing agent 0.5-3 parts 20-40 parts of water.

2. The earthquake-resistant and corrosion-resistant lightweight composite building material according to claim 1, characterized in that: The cement is ordinary Portland cement, and its strength grade is not less than 42.

5.

3. The earthquake-resistant and corrosion-resistant lightweight composite building material according to claim 1, characterized in that: The lightweight aggregate is expanded perlite, and its bulk density is not more than 200kg / m 3 , and the particle size distribution is between 0.5mm and 5mm.

4. The earthquake-resistant and corrosion-resistant lightweight composite building material according to claim 1, characterized in that: The corrosion-resistant fiber is glass fiber in the form of untwisted or slightly twisted continuous filaments, with a single filament diameter ranging from 6 microns to 24 microns, a fiber strength of not less than 3000 MPa, and an elongation at break controlled between 1.5% and 3.5%.

5. The earthquake-resistant and corrosion-resistant lightweight composite building material according to claim 1, characterized in that: The high molecular polymer resin is a modified epoxy resin, which is modified from the following components in parts by weight, and comprises the following steps: 1) Select epoxy resin base material: 100 parts of bisphenol A epoxy resin is used as the base material, and its epoxy equivalent is 180-200g / eq; 2) Adding a flexible segment modifier: Add 10-30 parts of polyethylene glycol PEG-4000 to the epoxy resin base material, and mix them evenly by mechanical stirring or heating and melting to improve the flexibility and impact resistance of the resin; 3) Adding toughening agent: Add 5-15 parts of core-shell rubber particles as toughening agent, and evenly disperse them in the resin by high-speed mixer or ultrasonic treatment to further enhance the toughness and shock resistance of the resin; 4) Mixing flame retardant: Add 1-5 parts of brominated epoxy resin flame retardant; 5) Adding catalyst: Finally, add 0.5-2 parts of catalyst dimethylbenzylamine to promote the curing reaction of epoxy resin; 6) Mixing and curing: After all the above components are mixed evenly, the resin system is cross-linked and cured by heating at 80-120°C to form a modified epoxy resin.

6. The earthquake-resistant and corrosion-resistant lightweight composite building material according to claim 1, characterized in that: The anti-seismic enhancer is waste tire rubber particles with a particle size between 0.5 mm and 2 mm.

7. The earthquake-resistant and corrosion-resistant lightweight composite building material according to claim 1, characterized in that: The preservative is a composite inorganic-organic preservative, comprising zinc salts, silicates and organic amine compounds; preferably, it includes: zinc borate, accounting for 35% of the total amount of the preservative, used to inhibit the growth of microorganisms and provide long-term antibacterial protection; sodium metasilicate, accounting for 25% of the total amount of the preservative, enhancing the structural strength of the building material and improving corrosion resistance; dodecyl dimethyl benzyl ammonium chloride, accounting for 15% of the total amount of the preservative, synergistically acting with the inorganic components to form a comprehensive anti-corrosion barrier.

8. The earthquake-resistant and corrosion-resistant lightweight composite building material according to claim 1, characterized in that: The water reducing agent is a high-efficiency polycarboxylic acid-based water reducing agent, and the water reducing rate is not less than 25%.

9. The method for preparing the earthquake-resistant and corrosion-resistant lightweight composite building material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1 Raw material preparation: weigh cement, lightweight aggregate, corrosion-resistant fiber, high molecular polymer resin, seismic enhancer, preservative, water reducer and water according to the formula; S2 Mixing and stirring: First, cement, lightweight aggregate, seismic reinforcement and corrosion-resistant fiber are added into a mixer for preliminary mixing, and the stirring speed is controlled at 100-200rpm to avoid fiber breakage; Then, slowly add water while continuing to stir to ensure that all solid ingredients are fully wetted; Next, add the prepared high molecular polymer resin and continue stirring until the resin is evenly dispersed in the mixture; Finally, add the preservatives and water reducer and stir thoroughly again to ensure that all ingredients are evenly mixed; S3 molding and curing: Pour the mixed material into the mold and shape it according to the required shape and size; Properly vibrate the mold to eliminate bubbles in the material and improve the density of the building material; Place the mold in a constant temperature and humidity environment for natural curing or heating curing, with the temperature controlled between 80-120°C until the building material is completely cured; S4 post-processing: After curing is complete, the building material is removed from the mold and necessary trimming and cutting is performed.

10. Use of the earthquake-resistant and corrosion-resistant lightweight composite building material according to any one of claims 1 to 8 in high-rise buildings, underground projects, marine and chemical facilities, bridge and road projects and special buildings.